A framework for multi-platform simulation of reinforced concrete structures. (15th February 2019) - Sadeghian, Vahid; Kwon, Oh-Sung; Vecchio, Frank
Highlights: A framework for multi-platform simulation of complex RC structures is presented. It enables to accurately consider both the global and local behaviour of the structure. It eliminates analysis calibrations commonly used for modelling complex structures. The application of the method was investigated using various types of case studies. Abstract: This study presents a framework for multi-platform analysis and hybrid simulation of reinforced concrete (RC) structures. In this approach, each subpart of the structure, based on its mechanical characteristics, is modelled using the most suitable finite element analysis tool or represented with a test specimen. The proposed framework combines all the substructure modules and takes into account the interactions between them by satisfying compatibility and equilibrium requirements. The main contribution of the study lies in demonstrating the effectiveness of multi-platform modelling in accurate and practical analysis of complex RC structures or multi-disciplinary RC systems with a particular focus on shear behaviour. Three application examples including a wide-flange shear wall, a three-storey frame with critical joints, and a soil-structure interaction simulation are discussed in detail. It is concluded that the multi-platform analysis can compute the behaviour of such structures with a level of accuracy that was previously difficult to achieve with most single-platform analysis software.